2015
DOI: 10.1007/s00436-015-4411-5
|View full text |Cite
|
Sign up to set email alerts
|

A histological evaluation of development and axis formation in freshwater fish ectoparasite Argulus bengalensis Ramakrishna, 1951 (Crustacea: Branchiura)

Abstract: The present investigation was carried out to underscore the developmental events of a crustacean ectoparasite of fish, Argulus bengalensis. Serial histological sections of the embryo were made at lateral, sagittal and longitudinal planes to explain its cleavage, gastrulation and axis specification. The centrolecithal egg of A. bengalensis underwent meroblastic superficial cleavage. The cleavage initiated at the future dorsal side of the egg within 5 h to 5 h and 30 min of incubation. Consequently, a small mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The appearance of P. roseola on the egg strips, under both laboratory and field conditions, proves that this rotifer population is a natural inhabitant of the farm water; the same fact was also noted by Fayer et al [7]. At the time of laying, each egg clutch is covered with a secretion from the paired collateral glands [8], which subsequently solidifies into a jelly coat [9]. According to Davis [10], the larvae hatch by creating a furrow through the egg envelopes using their dorsal organs as well as by increasing the osmotic swelling of the inner egg membrane.…”
Section: Discussionsupporting
confidence: 71%
“…The appearance of P. roseola on the egg strips, under both laboratory and field conditions, proves that this rotifer population is a natural inhabitant of the farm water; the same fact was also noted by Fayer et al [7]. At the time of laying, each egg clutch is covered with a secretion from the paired collateral glands [8], which subsequently solidifies into a jelly coat [9]. According to Davis [10], the larvae hatch by creating a furrow through the egg envelopes using their dorsal organs as well as by increasing the osmotic swelling of the inner egg membrane.…”
Section: Discussionsupporting
confidence: 71%
“…The egg laying process of the species recorded in a prior study (Banerjee et al, 2015a) revealed that median oviduct serves as a transit passage for the eggs but does not retain the eggs inside. As the collateral accessory glands open into this passage, it is hypothesized, that while passing through it, the eggs are embedded in the glandular secretion.…”
Section: Discussionmentioning
confidence: 98%
“…Rapid proliferation of the glandular cells is evident from the dynamic states of the nuclei which add further proof regarding the holocrine nature of the gland. The secretion of this gland presumably contributes to the jelly coat which subsequently solidifies (Banerjee et al, ) to form the outer egg envelop enabling the egg clutch to adhere onto the substratum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations